2020
DOI: 10.1111/faf.12455
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes

Abstract: Canopy-forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life-history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta-analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 98 publications
2
74
0
Order By: Relevance
“…In tropical coral reef ecosystems, nonreef habitats include, but are not limited to mangrove forests, seagrass meadows, and macroalgal beds. Though each habitat offers unique and essential ecosystem services, there is ample and increasing evidence that these nonreef habitats are important to coral reef fishes (Boström et al., 2011; Fulton et al., 2019; Nagelkerken et al., 2015; Pittman & Olds, 2015) and, at least in some places, coral reef fisheries (Fulton et al., 2020; Honda et al., 2013). Diel, tidal, and seasonal migrations of large‐bodied fishes (Haemulids, Lutjanids, and Lethrinids) from coral reefs to seagrass and mangrove habitats to forage and spawn are well documented (Appeldoorn et al., 2009; Honda et al., 2016; Huijbers et al., 2015; Nagelkerken et al., 2000; Verweij et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In tropical coral reef ecosystems, nonreef habitats include, but are not limited to mangrove forests, seagrass meadows, and macroalgal beds. Though each habitat offers unique and essential ecosystem services, there is ample and increasing evidence that these nonreef habitats are important to coral reef fishes (Boström et al., 2011; Fulton et al., 2019; Nagelkerken et al., 2015; Pittman & Olds, 2015) and, at least in some places, coral reef fisheries (Fulton et al., 2020; Honda et al., 2013). Diel, tidal, and seasonal migrations of large‐bodied fishes (Haemulids, Lutjanids, and Lethrinids) from coral reefs to seagrass and mangrove habitats to forage and spawn are well documented (Appeldoorn et al., 2009; Honda et al., 2016; Huijbers et al., 2015; Nagelkerken et al., 2000; Verweij et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that lagoonal habitats are important for the demographic success of tropical herbivores expanding into temperate ecosystems. Canopy‐forming seaweed and seagrass are important foraging and nursery habitats for many fish (Fulton et al., 2020; Zarco‐Perello & Enríquez, 2019). Several species of rabbitfish, including Siganus fuscescens , are strongly linked to tropical seagrass meadows, where they recruit in large numbers annually (Ambo‐Rappe et al., 2013), sustaining commercial fisheries that harvest up to 170 tonnes per year in some places (Soliman & Yamaoka, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that turf‐dominated reefs can promote the persistence of range‐extending tropical herbivorous fish, because they have a tendency to occupy habitats with less canopy (Bennett et al., 2015; Hoey & Bellwood, 2011). However, fish species also need nursery grounds that provide suitable environments for recruitment, such as seagrass meadows and algal beds (Fulton et al., 2020; Zarco‐Perello & Enríquez, 2019). To date, nursery habitats have not been integrated in the ecological model of the tropicalization of temperate reefs.…”
Section: Introductionmentioning
confidence: 99%
“…Positioning of macroalgal patches within the seascape clearly in uences diversity and abundance of sh assemblages (van Lier et al, 2018; Sievers et al, 2020), although preference for speci c macroalga genera (Lim et al, 2016;Wenger, Lier and Fulton, 2018) or physical structures (Wilson et al, 2017;Fulton et al, 2020; Tang, Graba-Landry and Hoey, 2020) by some sh will also effect the composition of macroalgal associated sh assemblages. Macroalgal composition and structure is especially important for the many sh that recruit to macroalgal habitats, including taxa that are targeted by sheries as adults and/or preform important ecologically roles (Wilson et al, 2010;Evans et al, 2014;Tano et al, 2016).…”
Section: Discussionmentioning
confidence: 99%